Improvement of coating durability, interfacial adhesion and compressive strength of UHMWPE fiber/epoxy composites through plasma pre-treatment and polypyrrole coating. (18th May 2016) - Jin, Xin; Wang, Wenyu; Xiao, Changfa; Lin, Tong; Bian, Lina; Hauser, Peter
Abstract: Ultra-high-molecular-weight polyethylene (UHMWPE) fibers have exceptionally higher specific strength and stiffness compared with other high-performance fibers. However, the interfacial adhesion and compressive performance of UHMWPE fiber-reinforced polymer composites (FPCs) are extremely low. The challenges are to achieve load transfer at the interface between the fiber and matrix at a molecular level. Here, we show that plasma pre-treatment of UHMWPE fibers followed by coating with polypyrrole (PPy) results in an 848% improvement in the interfacial adhesion and 54% enhancement in compressive performance. This method takes advantage of a toughening mechanism observed in spider silk and collagen, which the hydrogen bond power the load transfer. The results showed that these improvements of interfacial adhesion and compressive strength were attributed to hydrogen-bonding interactions between the plasma pre-treated UHMWPE and PPy, which improves the fiber–matrix–fiber load transfer process. In addition, the hydrogen-bonded PPy coatings also endowed durability electrical conductivity properties of the UHMWPE fiber.